Taking the LEAP with the Oculus HMD and CAD - Plucking at thin Air?. (2015) - Beattie, Nathan; Horan, Ben; McKenzie, Sophie
Abstract: Achieving adequate visualisation of designs within CAD packages remains a challenge for designers with current methods of 3D CAD visualisation requiring either a high level of technical ability, or expensive hardware and software. The recent re-emergence of consumer VR has lowered the barrier for everyday developers wanting to visualise their designs in true 3D. This paper presents the CAD Interaction Lab (CIL) which employs the Oculus Rift Head Mounted Display (HMD) and Leap Motion Controller (LMC) to provide a low cost method enabling users to use their hands to dissect a mechanic model to manipulate and inspect individual components in realistic 3D. Qualitative observations of user interactions with the CIL show that users were able to intuitively manipulate the CAD model using natural hand movements with only minimal instruction.